Analisis Efektivitas Program Pembinaan Kemandirian dalam Penerimaan Negara Bukan Pajak (PNBP) Lapas Perempuan Kelas II A Pekanbaru - Ningrum, Dewi Kusuma; Sari, Lapeti; Utami, Bunga Chintia (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to find out how the effectiveness the independence development program carried out in Pekanbaru women's prison in 2021-2023 is reviewed from PNBP and what types of activities contribute the most to PNBP in 2021-2023. This type of research is quantitative and descriptive. Based on the results of the study, the independence development program reviewed from non-tax state revenue is classified as a very effective criterion with a percentage of 112.3 percent and the type of activity in the coaching program that contributes the most to PNBP is the coaching of Tataboga with a percentage of 32 percent classified as a fairly good criterion and sewing with a percentage of 30 percent which is included the criteria is quite good. The level of effectiveness of the coaching program and the program's contribution to PNBP illustrates the success of the Pekanbaru women's prison in implementing the independence development program